2008
DOI: 10.2991/ijcis.2008.1.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Strategic R&D Projects for Car Manufacturers Based on the Evidential Reasoning Approach

Abstract: Assessment of strategic R&D projects is in essence a multiple-attribute decision analysis (MADA) problem. In such problems, qualitative information with subjective judgments of ambiguity is often provided by people together with quantitative data that may be imprecise or incomplete. A few approaches can be used to deal with such quantitative and qualitative MADA problems under uncertainty, such as the evidential reasoning (ER) approach that has its own unique features. In this paper, the ER approach is applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…As it was mention in our research objectives, the challenge is how to use two sources of information, and investigate them under a single framework to support the prioritization of the level of adoption of analytical tools in companies while losing or distorting information is prevented. In Yang et al (2011), and Liu et. al (2008) is demonstrated that expert judgments are routinely used in industry for interpreting data from surveys.…”
Section: A Common Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…As it was mention in our research objectives, the challenge is how to use two sources of information, and investigate them under a single framework to support the prioritization of the level of adoption of analytical tools in companies while losing or distorting information is prevented. In Yang et al (2011), and Liu et. al (2008) is demonstrated that expert judgments are routinely used in industry for interpreting data from surveys.…”
Section: A Common Frameworkmentioning
confidence: 99%
“…There are plenty of documented cases, on which sophisticated analytical tools are applied on this industry, for example the petroleum and plastic industries. More specifically, in Liu et al (2008) it is documented the use of multi criteria decision making methods in order to assess different projects. Usually, starting a new R&D project implies important amounts of economic recourses.…”
Section: The Analytical Tools In Research and Developmentmentioning
confidence: 99%